A Comment Study of Li Ziqi’s Cultural Short Videos in Light of Attitude System - Zhang, Congying; Liu, Lingling (Journal of Theory and Practice in Humanities and Social Sciences, 2025)
In the digital age, short videos have emerged as a vital medium for cross-cultural communication, exemplified by Li Ziqi’s cultural content, which bridges Chinese traditions with global audiences. While prior studies focused on video content analysis, this research addresses the gap in comparative sentiment analysis of viewer comments across domestic and international platforms. Grounded in J.R. Martin’s Attitude System theory, this study examines 40 top-liked comments from Bilibili (domestic) and YouTube (foreign) to explore affective attitudes and value recognition. Through word frequency analysis and text classification, findings reveal overwhelmingly positive sentiments on both platforms. Domestic comments emphasize cultural identity and nostalgia through keywords like “traditional” and “family warmth,” reflecting localized narratives. In contrast, foreign comments prioritize universal aesthetics and cross-cultural resonance, particularly highlighting admiration for Chinese philosophical values such as “quiet” “filial piety” and “self-sufficiency”. The study demonstrates how Li Ziqi’s micro-narratives transform abstract Chinese values into tangible cultural symbols, fostering emotional engagement. By expanding the application of the Attitude System framework to short video discourse, this research offers novel insights into enhancing the global dissemination of Chinese culture, underscoring the interplay between cultural specificity and universal appeal. Limitations include sample representativeness and multimodal analysis gaps, suggesting avenues for future inquiry.